The Effect of CERDIK-Based Leaflet Health Education on the Knowledge Level of Hypertensive Patients in a Primary Health Center - A. Ulfiana Fitri; Nabila Gita Salsabila; Irwandi Rachman (SIGn Journal of Public Health, 2026)
Hypertension is a growing global health issue, triggered by poor self-management and patient non-adherence to treatment due to a knowledge deficit. At the primary care level, such as Tamamaung Public Health Center, high morbidity rates indicate the urgency for targeted health promotion strategies. Although educational approaches are frequently implemented, the integration of the national CERDIK message into specific print media for outpatients remains highly limited. This study aimed to analyze the effect of CERDIK-based leaflet education on the knowledge level of hypertensive patients at Tamamaung Public Health Center. A pre-experimental, one-group pretest-posttest design without a control group was employed, involving 30 respondents selected through an accidental sampling technique. Data collection was conducted in three stages (pretest, posttest 1, and posttest 2) using a structured questionnaire, and the data were analyzed using the nonparametric Wilcoxon Signed Ranks Test. The results demonstrated that the educational intervention was highly effective in significantly increasing knowledge scores at posttest 1 (p<0.001; mean difference=30.83). Although the long-term evaluation revealed a significant decrease in information retention (p=0.003; mean difference=7.83), the final achievement at posttest 2 remained significantly higher (p<0.001; mean difference=23.00) than in the baseline condition. In conclusion, the educational intervention utilizing the printed CERDIK leaflet had a highly positive effect on the patients’ cognitive understanding. These findings suggest the need for message reiteration and continuous monitoring at the community level to mitigate memory decay and facilitate more effective patient lifestyle modifications.